MENTAL HEALTH PROBLEMS IN ANTARCTICA - Gunderson, E. K. (1967)
Health problems are of special concern at small Antarctic stations because of the extreme environmental conditions and because of complete isolation from the outside world during the winter months. Incidences of common symptoms, reflecting insomnia, anxiety, depression, and hostility increased significantly during the winter months in three recent Antarctic expeditions. These results confirmed earlier findings obtained during the IGY period. A number of personal history and personality variables were found to correlate significantly with two criteria of emotional adjustment: (1) ratings of emotional stability by supervisors and peers at Antarctic stations, and (2) symptom scores from a questionnaire filled out twice during the winter. Relationships of psychiatric screening information to the emotional adjustment criteria varied with occupational group, particular criterion measure, and time of year. Presented at Symposium on Circumpolar Health Related Problems, University of Alaska, College, Alaska. Revision of report dated 25 Jul 1967.